Deciphering yield modification of hadron-triggered semi-inclusive recoil jets in heavy-ion collisions - Yang He; Maowu Nie; Shanshan Cao; Rongrong Ma; Li Yi; Helen Caines (Physics Letters B, 2024)
In relativistic heavy-ion collisions, a hot and dense state of matter, called the Quark-Gluon Plasma (QGP), is produced. Semi-inclusive jets recoiling from trigger hadrons of high transverse momenta (pT) can serve as an effective probe of the QGP properties, as they are expected to experience jet quenching when traversing the QGP. Recent experimental results on the ratio of recoil jet yields normalized by the trigger counts in heavy-ion collisions to that in p+p collisions (IAA) pose an unexpected challenge in its interpretation. It is observed that IAA rises with the jet pT and possibly exceeds unity at high pT, while traditionally it is expected that jet quenching would lead to IAA<1. To address this challenge, we utilize the Linear Boltzmann Transport (LBT) model to simulate jet transport in the QGP, and study the effect of jet quenching for high-pT triggers and recoil jets separately on IAA. We find that the quenching of the colored triggers alone is responsible for the rising trend and larger-than-unity value observed experimentally.